Évangéliser par le corps. La policía cristiana dans les Andes au XVIe siècle - Jérome Thomas (Cahiers d'Études du Religieux- Recherches Interdisciplinaires)
In the sixteenth century, missionaries wanted to educate people of the Andes under Spanish rule according to Christian standards so that they repress their bodily manifestations and learn modesty. A corpus of texts, sermons, theoretical writings attacked what appeared to return to savagery. These requirements are known to policía cristiana which means the Spanish desire to evangelize and to civilize the natives. Whether in the area of attitudes, gestures or the habitat, the notion of obligation toward the Indians to live like civilized men. Imposed by the Church and the colonial administration, the policía cristiana ran into multiple resistances.